Optimal Indirect and Capital Taxation - Golosov, Mikhail; Kocherlakota, Narayana; Tsyvinski, Aleh (Review of Economic Studies, 2003)
In this paper, we consider an environment in which agents ’ productivities are private information, potentially multi-dimensional, and follow arbitrary stochastic processes. We allow for arbitrary incentive-compatible and physically feasible tax schemes. We prove that it is typically Pareto optimal to have positive capital taxes. As well, we prove that in any given period, it is Pareto optimal to tax consumption goods at a uniform rate. All, University of Minnesota and the Federal Reserve Bank of Minneapolis. Kocherlakota acknowledges the